The Influence of The Characteristics of Zakat Financial Information on The Quality of Financial Reports of Zakat Institutions in Riau - Saputra, Wali; Bakri, Bakri (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to analyze the effect of the characteristics of zakat financial information on the quality of financial reports of zakat institutions in Riau. This study uses primary data obtained by distributing questionnaires to 204 stakeholders who always interact with zakat institutions. Data analysis methods used in this study include research instrument testing and hypothesis testing using multiple regression analysis. The results of this study concluded that partially the characteristics of zakat financial information